Reliability assessment of pultruded FRP reinforcements with embedded fiber optic sensors - Kalamkarov, Alexander L.; MacDonald, Douglas O.; Georgiades, Tasos (My University, 2000)
Fiber optic strain sensors are successfully embedded in glass and carbon fiber reinforced polymer (GFRP and CFRP) reinforcements during pultrusion. The specific application is the use of the smart composite reinforcements for strain monitoring of innovative civil engineering structures. A comprehensive reliability assessment of the pultruded smart FRP rods with embedded sensors is performed, encompassing mechanical tests at room temperature as well as under conditions of low and high temperatures. In these tests, the strain output from the embedded fiber optic sensors was in good agreement with the output from surface mounted extensometers. The fatigue and short-term creep behavior of the smart composite rods is also examined. Finally, the long-term performance of the smart composites under sustained loads in alkaline environments simulating conditions encountered in concrete structures is assessed. The experiments conducted showed that the strain from the embedded fiber optic sensors conformed well with the corresponding output from the extensometers or foil gages. (C) 2000 Elsevier Science Ltd. All rights reserved. Fiber optic strain sensors are successfully embedded in glass and carbon fiber reinforced polymer (GFRP and CFRP) reinforcements during pultrusion. The specific application is the use of the smart composite reinforcements for strain monitoring of innovative civil engineering structures. A comprehensive reliability assessment of the pultruded smart FRP rods with embedded sensors is performed, encompassing mechanical tests at room temperature as well as under conditions of low and high temperatures. In these tests, the strain output from the embedded fiber optic sensors was in good agreement with the output from surface mounted extensometers. The fatigue and short-term creep behavior of the smart composite rods is also examined. Finally, the long-term performance of the smart composites under sustained loads in alkaline environments simulating conditions encountered in concrete structures is assessed. The experiments conducted showed that the strain from the embedded fiber optic sensors conformed well with the corresponding output from the extensometers or foil gages.
Keywords: Fiber optics; Pultrusion; Creep testing machines; Detectors